Bird's eye view, Port of Spain, Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
Photo showing an aerial view of the buildings and vegetation in Port of Spain, Trinidad. The postcard bears handwritten correspondence and a one cent United States postage stamp.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; 1910; Dwellings--Trinidad and Tobago